Analysis of induction-based thermal demagnetization of a permanent magnet rotor in the context of recycling - Ihne, Thorsten; Wieprecht, Nico; Hahn, Roman; Franke, Jörg; Kühl, Alexander (2023 13th International Electric Drives Production Conference, 2023)
Rare Earth (RE) Magnets are a key for many green technologies causing continuously increasing demand in the European Union (EU). Alongside motors for e-mobility and generators in wind turbines, compressors in domestic heat pumps represent a potential lever for slowing climate change. On the other hand, the dominant market power of the PR China results in a high supply chain risk. Therefore, the EU has declared these elements as critical raw materials of the highest category and plans a compulsory recycling share of 15% until 2030. Currently, no systematic recycling activities for RE magnets are operated on an industrial scale. In the present paper a concept for the extraction of RE magnets from rotors of HVAC compressors is presented. The focus is set on the thermal in-situ demagnetization by induction which is crucial for the disassembly of the magnets. This process ensures efficient heating to temperatures above the individual Curie temperatures so that interfering reaction forces are eliminated. Systematic test series are carried out based on an experimental set-up to identify the main process parameters and restrictions. The achieved results are analyzed and are evaluated regarding the transferability to a potential series process.<br

Approaches For The Physical Sorting Of Soft And Hard Magnetic Material Mixtures In The Context Of Rare Earth Recycling - Ihne, Thorsten; Hahn, Roman; Kühl, Alexander; Franke, Jörg (Proceedings of the CPSL 2024., 2024)
Rare earth (RE) elements applied for magnets are considered as critical raw materials by most industrial countries. On the one hand especially neodymium-iron-boron (NdFeB) magnets are essential for the current economic transformation as they are used for core technologies such as electric mobility and wind power causing continuously increasing demand. On the other hand, there is a significant supply chain risk due to poor market diversification and bad substitutability. This leads to various economic problems such as steady rising prices, price volatility and potential shortages. In addition, the primary production has a poor ecological footprint. In this context, the recycling of NdFeB magnets has a high economic, geopolitical and ecological potential. However, hardly any recycling is currently carried out on industrial scale due to technical and organizational difficulties. As magnetic extraction from end-of-life (EOL) products by dismantling is only economically feasible in specific cases, the implementation of a universally applicable process based on shredding and multi-stage sorting is essential. Intensive research is currently being carried out for the further processing of the pure NdFeB granulate, but there is a lack of reliable separation processes for the hard and soft magnetic components of the ferrous shredding fraction, which are similar in terms of many physical properties. Therefore, the present paper discusses approaches based on physical sorting principles to close the existing gap in the overall process chain. The solution preferred by the authors is based on a multi-stage process chain realized as a flow process, which primarily exploits differences with regard to the mechanical and magnetic characteristics.<br
Keywords: Rare Earth Magnets; Critical Raw Materials; Recycling; Physical Sorting; Hard And Soft Magnetic Materials

Approach for Advanced Mechanical Recycling Strategies of Rare Earth Magnets Applied in Traction Drives - Ihne, Thorsten; Hahn, Roman; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (Production at the Leading Edge of Technology, 2023)
Rare Earth (RE) Magnets are crucial for the green transition of the European Union (EU). This applies especially for e-mobility where RE magnets are used for highly efficient traction drives. Permanent magnetic motors offer the best efficiency, but the use of Rare Earth Elements (REEs) is related to several drawbacks. The magnets and the required raw materials are almost exclusively imported. This causes problems for European industry due to supply chain risks and continuously increasing prices. In addition, primary production is associated with a poor ecological footprint. Therefore, the EU has declared REs as critical raw materials with highest supply chain risk and plans a compulsory recycling share of 15% until 2030. Currently, no industrially applicable processes exist for systematic recovery of RE magnets. In this context the following paper should present approaches for an automated process chain starting with an end-of-life traction drive until the extracted and demagnetized magnets.<br
Keywords: Rare earth magnets; Recycling; Traction drives; Critical raw materials

Approach For Optimized Dismantling Strategies And Design For Recycling Of Electric Traction Drives - Hahn, Roman; Wieprecht, Nico; Ihne, Thorsten; Kühl, Alexander; Franke, Jörg (6th Conference on Production Systems and Logistics, 2024)
With the widespread adoption of electric vehicles (EVs), there arises a pressing need for sustainable processing of electric traction drives (ETDs) at the end of their life cycles. Current methods for dismantling and recycling ETDs often show inefficiencies in material recovery causing economic disadvantages and increased environmental impact. Of particular relevance is the recycling of rare earth (RE) magnets, which are extensively used in ETDs because of their superior magnetic properties. Given the scarcity of rare earth elements (REEs) and the environmental impact associated with their extraction, the need for efficient RE magnet recycling is of key importance. However, there is currently a lack of efficient dismantling processes and recyclability is often inadequate. By developing an optimized approach that focuses on adapted dismantling strategies and design for recycling, a critical gap in the sustainable production and disposal of electric vehicles will be closed. A crucial aspect is the design for recycling, enabling efficient recovery and reuse of materials and components. The approach presented in this paper combines different aspects such as material composition, modularity of components, standardization and good separability to optimize the design for recycling of ETDs. By providing optimized dismantling strategies as well as guidelines for the design for recycling, the transition to more environmentally sustainable transport systems is supported in addition to increased economic efficiency. <br
Keywords: Recycling; Reuse; Optimized Dismantling; Design for Recycling; Electric Traction Drives; Rare Earth Magnets; Permanent Magnet Synchronous Machine

A Review of Electromagnetic Simulation and Modelling Approaches for the Research on Axial Flux Synchronous Machines - Schäfer, Adrian; Pecha, Urs; Parspour, Nejila; Kampker, Achim; Born, Henrik; Hartmann, Sebastian; Franke, Jörg; Baader, Marcel; Hahn, Roman (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
Extensive electromagnetic (EMAG) studies are necessary to fully realize the potential of axial flux machines (AFMs). However, the disc-shaped air gap and the complex three-dimensional path of magnetic flux pose challenges in modelling AFMs compared to conventional radial flux machines. This study reviews current research on EMAG modelling and simulation of AFMs, highlighting the need for tools that address AFM-specific effects. Existing approaches are analysed based on the requirements composed by fundamental objectives of EMAG simulations and AFM-specific effects, revealing limitations in flexibility and the ability to capture emerging trends in the field of AFMs. While computationally expensive 3D finite element analysis (FEA) offers comprehensive flexibility in EMAG modelling, it lacks efficiency to carry out extensive studies on such trends. Therefore, there is a need to either further accelerate 3D FEA or to increase the flexibility of existing alternatives to facilitate and thereby promote research in the field of AFM and other 3D flux machines. While the integration of some production-specific effects, such as manufacturing tolerances, already is investigated for EMAG simulations of AFMs the future research on the early estimation of manufacturability based on EMAG simulations is crucial for evaluating designs and anticipating manufacturing influences.<br
CRIS-Team Scopus Importer:2024-08-02
Keywords: Solid modeling; Magnetic flux; Three-dimensional displays; Reviews; Windings; Production; Market research; axial flux machine; electromagnetic simulation; literature review; multi-domain; manufacturing effects

Comprehensive Review and Systemization of the Product Features of Axial Flux Machines - Kampker, Achim; Born, Henrik; Hartmann, Sebastian; Drexler, David; Franke, Jörg; Baader, Marcel; Hahn, Roman; Parspour, Nejila; Schäfer, Adrian; Pecha, Urs (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
With the increasing electrification of the powertrain across all mobility applications, the requirements for electric motors are becoming more and more diverse: Depending on the application, the requirements for power and torque vary greatly while at the same time keeping costs, weight and installation space must be kept to a minimum. While the radial flux design has established itself for electric traction drives in the market, axial flux motors also provide great potential for vehicles with high torque requirements and small installation space. The axial arrangement of the components within this topology allows many degrees of freedom in product design, which results in many sub-variants of axial flux motors. However, there is a lack of a uniform and consolidated categorization of these variating design features in both scientific literature and industrial practice. In this work, the different design features of axial flux motors were identified based on an extensive as well as systematic literature research and categorized according to uniform characteristics. As a result, the complex variety of different axial flux motor variants is systematized and standardized, which lays the foundation for a uniform categorization of this motor topology.<br
Keywords: Torque; Systematics; Windings; Space cooling; Stator windings; Production; Motors; electric motor; electric motor production; axial flux motor; literature review; systemization; product; topology study; systematic review; categorization

Evaluation of different methods for removing the conductor insulation of stranded conductors - Riedel, Andreas; Hahn, Roman; Kühl, Alexander; Franke, Jörg (12th International Symposium on Advanced Topics in Electrical Engineering, ATEE 2021, 2021)
The ecological change in society and politics leads to an increased demand for alternative drives. In the field of mobility, this can be observed by ongoing innovations in research and development as well as in the production of electric machines. Currently, the automotive industry is focusing more and more on traction drives using hairpin technology. The reasons for this are the easier automation of the manufacturing process and the higher copper filling factors that can be achieved. The latter help to improve the power density. At high frequencies, which inevitably occur in high-speed applications, large conductor dimensions lead to additional losses due to eddy currents. To reduce these losses, twisted round wires can be used instead of flat conductors. Nevertheless, the manufacturing as well as the processing of this semi-finished product is more complex. The aim of this paper is to present and compare the possibilities for removing the required tape of the stranded conductor and to substantiate it with initial results. For this purpose, the general production chain of a hairpin stator is explained at the beginning of the paper in order to show the reasons why the removal of the bandage is of elementary importance. This is supplemented by technological aspects of stranded wire technology which cause-effect relationships serve as the basis for the main part of this paper.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Electric traction drives; Hairpin winding; Insulation material; Litz wire; Skinning methods; Stranded conductors

Experimental Parameter Analysis for the Induction based thermal Demagnetization of PM Rotors from Electric Traction Drives - Hahn, Roman; Ihne, Thorsten; Baader, Marcel; Franke, Jörg; Kühl, Alexander; Risch, Florian (2025 IEEE International Electric Machines & Drives Conference (IEMDC), 2025)
In the context of decarbonization, electromobility is currently undergoing a strong global expansion, whereby up to 75 million vehicles could be electrically powered by 2035. Ensuring the supply of necessary raw materials is crucial for this development. Electric vehicles require critical raw materials not only for batteries but also for the traction drives. Due to their advantageous properties, permanent magnet (PM) motors containing rare earth (RE) magnets are mostly applied. The required RE elements are considered as critical raw materials due to their highly vulnerable supply. In parallel, their primary production has a high ecological footprint. In this context, recovery of RE magnets from traction drives is a key to ensure a resilient and sustainable supply chain. Corresponding extraction processes are currently the subject of research, whereby demagnetization is always obligatory. For this purpose, a process based on inductive heating of complete rotors is proposed and systematically analyze
Keywords: recycling; electric traction drives; permanent magnets; demagnetization; induction; circular economy

Optimized Recycling Strategy for Permanent Magnet Drives of Electric Vehicles with Focus on Rare Earth Magnet Extraction - Ihne, Thorsten; Hahn, Roman; Giesbert, Fabian; Baader, Marcel; Franke, Jörg; Risch, Florian (2025 IEEE International Electric Machines & Drives Conference (IEMDC), 2025)
Permanent magnet (PM) motors offer high efficiency and power density, resulting in a dominant market share for electric vehicles across all major markets. However, a significant drawback is the related use of rare earths (RE) in high-performance PMs, leading to high material costs and dependence on limited resources. The automotive industry is a major driver of demand for several RE elements, which have been classified as critical raw materials by numerous industrialized countries. Among other measures, the establishment of a circular economy can contribute to increasing resilience of supply and sustainability. To achieve this objective, organizational and technological prerequisites must be implemented. In this context, this paper presents an overall concept for the extraction of rare earth magnets from end-of-life vehicle drives. For this purpose, a multi-stage process chain is proposed. The individual process steps are evaluated and compared with alternatives, focusing on the magnet extraction from the roto
Keywords: Recycling; Rare Earth Magnets; PM Motors; Circular Economy; Dismantling

Recycling Concept for Electric Vehicle Drives in the Context of Rare Earth Recovery - Ihne, Thorsten; Hahn, Roman; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
Neodymium Iron Boron (NdFeB) magnets provide the best magnetic properties and are therefore key components for many green technologies. This leads to steeply rising demand for the related rare earth (RE) elements, with e-mobility as central driver. The supply situation for RE magnets is characterized by the dominance of the PR China for the entire value chain causing various problems for the European industry. A potential countermeasure to reduce the dependency on imports is the implementation of a closed raw material cycle within the European Union (EU). Especially the recycling of automotive traction drives provides high potential for the recovery of RE magnets but is complicated by various technical and organizational factors. As result currently no recycling is industrialized for the recovery of RE magnets from traction drives of end-of-life (EOL) electric vehicles (EV).In this context the following paper presents a general concept for the recovery of RE magnets from automotive traction motors. The focus is set on the extraction process of the magnets from the rotor and the related thermal demagnetization step. Finally, the achieved results are evaluated regarding the transferability to a potential series process.<br
Keywords: Electric potential; Europe; Rotors; Electric vehicles; Traction motors; Recycling; Magnets; Rare earth magnets; circular economy; recycling; electromobility; traction drives; thermal demagnetization

The Production Process Chain of Axial Flux Motors: A Comparative Study - Baader, Marcel; Hahn, Roman; Franke, Jörg; Kampker, Achim; Born, Henrik; Hartmann, Sebastian; Drexler, David; Parspour, Nejila; Schäfer, Adrian; Pecha, Urs (2024 1st International Conference on Production Technologies and Systems for E-Mobility (EPTS), 2024)
As the global transition to electrification and green energy intensifies, the significance of advanced electric motor technology grows. Axial flux motors (AFM) stand out with their unique design and inherent advantages, positioning them as a promising solution in this sustainability-driven shift. This paper presents a comparative analysis of the manufacturing process chain for AFMs, crucial components in diverse sectors such as electric vehicles, renewable energy systems, and industrial automation. AFMs offer distinct advantages over traditional radial flux motors, including high power density, compact size, and efficiency, underscoring the importance of optimizing their production process for enhanced performance and reliability. Beginning with an overview of AFM technology and its wide application potentials and topologies, the paper examines each stage of a potential manufacturing process chain. These stages encompass design and engineering considerations, winding techniques for stator components, fabrication methods for core laminations, and magnet assembly processes. By examining various methods and processes, their impact on impact on automation, manufacturability, production efficiency as well as quality will be assessed, and the crucial role of AFMs in promoting sustainable technological advancements across industries and in shaping a greener future is highlighted.<br
CRIS-Team Scopus Importer:2024-08-02
Keywords: Stator cores; Power system measurements; Manufacturing processes; Automation; Magnetic cores; Windings; Stator windings; electric motor; axial flux motor; manufacturing; electric motor production; process chain